Argumentation in high school from inquiry-based experimentation in Chemistry (Research, Society and Development, 2021)
Research in Science Education has been recommending attention to argumentative practices. The challenge is to look for activities that can stimulate this type of practice so that the students talk science, since it is considered to be beneficial to conceptual understanding and provide students with the ability to think critically in a scientific context. In this paper, it is discussed how 20 activities with inquiry-type experiments in chemistry can promote argumentation in high school students in the chemistry laboratory. This kind of experimentation approach give the students the opportunity to learn and appreciate the process of science. The activities were categorized according to the level of proximity to an investigative activity and also their degree of openness. The discourses during the activities were analyzed in order to identify arguments, according to Toulmin's argument pattern. The study showed that inquiry experimentation can be an effective platform to stimulate the production of arguments. Activities with a higher level of inquiry and openness had a greater impact on the production of arguments, especially those richer, according to the analysis tool chosen in the study.